Toxic Effects of Purified Microcystins from Soil Blue-Green Alga Oscillatoria pseudogeminata on Tomato Plant Lycopersicon esculentum (Baghdad Science Journal, 2019)
The current study included the isolation, purification and cultivation of blue-green alga Oscillatoria pseudogeminata G.Schmidle from soil using the BG-11liquid culture medium for 60 days of cultivation. The growth constant (k) and generation time (G) were measured which (K=0.144) and (G=2.09 days).Microcystins were purified and determined qualitatively and quantitatively from this alga by using the technique of enzyme linked immunosorbent assay (Elisa Kits). The alga showed the ability to produce microcystins in concentration reached 1.47 µg/L for each 50 mg DW. Tomato plants (Lycopersicon esculentum) aged two months were irrigated with three concentrations of purified microcystins 0.5 , 3.0 and 6.0 µg/L for 24 days. The results showed that the highest bioaccumulation of these toxins was found in the plant group treated with concentration 6.0 μg/L, with an average of 12.278 µg/L in the entire plant body, with a daily accumulation rate of 0.511 µg/day compared with control group and other treatments (p≤0.05). The highly accumulation of toxin was found in roots followed in descending order by stems and leaves respectively and were directly proportional to the increased concentration of purified microcystins. The study indicated that there were significant changes (p≤0.05) in the plant height, length of roots and surface area of the leaves and the leaves appeared pale green in color, which increased with increasing the concentration of purified toxin. The obtained results also showed a significant decrease in the concentration of carbohydrates and chlorophylls by increasing concentrations of purified toxins.